Synthesis and Characterization of Some New Azo-imine Dyes and their Applications - Hawaiz, Farouq E.; Raheem, Darya J.; Samad, Mohammed K. (Sulaimani Journal for Pure and Applied Sciences, 2016)
Some new azo-imine dyes have been synthesized via the diazotization of sulphanilic acid and its coupling reaction with salicylaldehyde giving a starting material 4-((3-formyl-4-hydroxyphenyl)diazenyl)benzenesulfonic acid. The later reacted with different substituted anilines to give the target azo-imine dyes [4-((3-((4-substitutedphenylimino)methyl)-4-hydroxyphenyl)diazenyl)benzenesulfonic acid] which were confirmed by using FT-IR, 1H-NMR and 13C-NMR spectra. The synthesized dyes are used for dyeing performance on acetate, cotton, nylon, wool, acrylic and polyester fibers, along with the effect of mordant on dyeing process. All the synthesized dyes gave moderate to excellent fastness properties on each fiber. The effect of cationic and anionic surfactants on the wash fastness has been studied.
Keywords: Azoimines; Dyeing; Mordant; Multifiber strip; Fastness